Qualidade percebida nos serviços de atendimento bancários em agências do banco do estado do Espírito Santo (Banestes S/A) da Grande Vitória - ES. - Arcemar Rocha de Christo (2001)
This work has as an objective search and analyze the perception of external clients in four bank agencies of Banco do Espírito Santo (BANESTES S/A) relating to the service quality offered by agencies located in the area of Grande Vitória, Estado do Espírito Santo. The Concept Model of Quality of Services, formulated by Parasuranan etal.(1985), and the subsequent refinements carried out from the original version, that resulted in the SERVQUAL scale constitute the theoretical basis in which this work defines. It was adopted the modified scale SERVQUAL, as it was applied in previous works, and maintained its original basic structure. All Quality Dimensions (Physical Aspects, Trustfulness, Readiness of Responses, Security and Trust and Empathy) were searched, aiming at identifying the perception level of client about the quality of services in four agencies in the area of Grande Vitória -ES, totaling two hundred and forty-nine clients. The main conclusions were: the general quality service of BANESTES S/A was evaluated between "equal expected" and "better than expected"; in the researched agencies the quality is a little above from expected with 3,65 average; observing the scores related to the five general dimensions of service quality constantsto the instrument SERVQUAL, the questions 1, 11 and 13 were identified, that compose the dimensions physical aspects and readiness of response, that were out of the acceptance group and received from the clients minimum grade equal 1; the evaluation through the general grade was 7,5 in a scale from 0 to 10.